Research of сorellations between the parameters of the craniocervical, nasopharyngeal complexes and the maxillofacial apparatus of patients with distal occlusion (literature review) - Сhumak Н. М.; Kostiuk Т. М. (Actual Dentistry, 2024)
Abstract. Every year, the amount of children with diseases of the upper respiratory tract, musculoskeletal system, and maxillofacial system is increasing. The child’s body is extremely sensitive to adverse factors affecting both the growth and development of the body in general and the skull in particular. Some researchers attribute the pathological state of the upper respiratory tract and musculoskeletal system to the factors of inhibiting development of the dentition-maxillary apparatus. The prevalence and severity of dentognathic deformities in children with an existing disbalance of the Musculo-skeletal complex is greater than in somatically healthy children and increases with age, which determines the necessity for timely and multi-stage rehabilitation of these patients. In order to research the pathogenetic corellations between the parameters of the skull and the cervical spine in children with complex pathology, 21 literary sources from the scientometric database of medical research-base “PubMed” for the period 2016–2024 were included in the review and analyzed, which shed light on the issue of complex treatment of patients with dentognathic deformities and existing accompanying pathology. The analysis of articles studying the lateral cephalograms of patients with complex pathology and existing class II dentognathic deformities confirmed the presence of a statistically reliable corellations between the parameters of the cervical spine and the parameters of the jaws, which is most pronounced during the period of peak growth of the facial skeleton. Studies that included three-dimensional morphometric analysis of cone-beam computed tomography of patients with distal occlusion and concomitant pathology confirm the interconnections of average strength between the parameters of the middle and lower parts of the upper respiratory tract and the length of the bodies of the jaws. The creation of a multifactorial model of the disease based on the development and implementation of a multidisciplinary algorithm for complex rehabilitation of patients with distal occlusion and existing pathology of the upper respiratory tract and cervical spine is necessary for the objective assessment of complex pathology, the creation of a joint plan with related specialists and the achievement of a stable treatment result.